(untitled) (JS (JURNAL SEKOLAH), 2021)
Abstract: Improving Student Learning Outcomes of English Subjects Through Picture Series in Class VIII-2 Middle School 1 Patumbak. The purpose of this study was to determine the extent of understanding and mastery of English subjects after the use of the use of picture series in Class VIII-2 students of SMPN 1 Patumbak 2018/2019 academic year. The research subjects were students of Class VIII-2 SMPN 1 Patumbak. The results of this study indicate that simple English learning using the applied introductory system is carried out through five stages of learning, namely (1) Introduce, (2) Second stage, Connect, (3) In the Apply stage, ( 4) The next stage is Reflect (5) Train students to describe something in the group. Keywords: English, picture series, learning outcomes Abstrak:Meningkatkan Hasil Belajar Siswa Mata PelajaranBahasa Inggris Melalui Picture Series Di Kelas VIII-2SMP Negeri 1 Patumbak.Tujuan penelitian ini adalah untuk mengetahui seberapa jauh pemahaman dan penguasaan mata pelajaran Bahasa Inggris setelah diterapkannya penggunaan picture series pada siswa siswa Kelas VIII-2 SMPN 1 Patumbak tahun pelajaran 2018/2019. Subyek penelitian adalah siswa-siswi Kelas VIII-2 SMPN 1 Patumbak. Hasil penelitian ini menunjukkan bahwa pembelajaran bahasa Inggris sederhana menggunakan sistim perkenalan terapan, dilakukan melalui lima tahapan pembelajaran yaitu (1) Introduce (Perkenalkan),(2) Tahap kedua, Connect (Hubungkan), (3) Pada tahap Apply (Terapkan),(4)Tahap berikutnya adalah Reflect (Refleksikan)(5) Melatih siswa mendiskripsikan sesuatu dalam kelompok. Kata kunci: Bahasa Inggris, picture series, hasil belajar